Vaccine-preventable anal human papillomavirus in Australian gay and bisexual men - I. Mary Poynten (Papillomavirus Research, 2017)
Objective: HPV causes ~90% of anal cancer and HPV16 is the type most commonly associated with anal cancer. Gay and bisexual men (GBM) are at greatly increased risk. We investigated patterns of vaccine-preventable anal HPV in older GBM. Methods: The Study of the Prevention of Anal Cancer (SPANC) is an ongoing, prospective cohort study of HIV-positive and HIV-negative Australian GBM. Participants completed questionnaires and underwent an anal swab for HPV genotyping using Roche Linear Array. We analysed baseline data from SPANC by HPV type, mean number of types, stratified by age and HIV status. Results: Anal HPV results from 606 (98.2%) of 617 participants (median age 49 years, 35.7% HIV-positive) showed 525 (86.7%) had â¥1 HPV type and 178 (29.4%) had HPV16. Over one third of participants (214, 35.3%) had no nonavalent vaccine-preventable types detected. Two (0.3%) participants had all quadrivalent types and none had all nonavalent vaccine types. HIV-positive participants (p<0.001) and younger participants (p=0.059) were more likely to have more vaccine-preventable HPV types detected. Conclusion: Anal HPV was highly prevalent in this largely community-based GBM cohort. Vaccine-preventable HPV16 was detected in approximately one third of participants. These findings suggest that the potential efficacy of HPV vaccination of older GBM should be explored. Keywords: Human papillomavirus, HPV, Anal, Vaccine, Prevalence, Gay and bisexual men, MSM, HIV